Lipidomics reveals the potential mechanism of honokiol against adenine-induced chronic kidney disease - Liu, Xinhui; Gao, Liwen; Huang, Xi; Deng, Ruyu; Wei, Xian; Lu, Jiandong; Li, Shunmin (Frontiers in Pharmacology, 2022)
Honokiol (HKL), a biphenolic compound, is derived from the bark of Magnolia officinalis, which is used in traditional Chinese medicine for gastrointestinal complaints. HKL has diverse pharmacological activities and has protective effects in various disease models. However, the role and mechanism of HKL in treating chronic kidney disease (CKD) remain unclear. This study was designed to investigate whether HKL can alleviate CKD and the potential mechanism by which it acts. Male Sprague-Dawley rats were fed 0.75% w/w adenine feed for 3 weeks to induce CKD. HKL was administered by gavage at a dose of 5 mg/kg/day for 4 weeks. Using a special kit, serum creatinine (Scr) and blood urea nitrogen (BUN) were measured. To assess renal pathology, periodic acid-Schiff and Masson’s trichrome staining were conducted. Renal lipid profiles were analyzed by ultra-high-performance liquid chromatography/mass spectrometry (UHPLC/MS). The results showed that the administration of HKL reduced Scr and BUN and alleviated renal tubular atrophy and tubulointerstitial fibrosis in an adenine-induced CKD rat model. By using lipidomics, we identified 113 lipids (47 lipids in negative ion mode, 66 lipids in positive ion mode) that could be significantly reversed by HKL treatment in CKD rat kidneys. Most of these lipids belonged to the phosphatidylcholine (PC), ceramide (Cer), phosphatidylethanolamine (PE), and triacylglycerol (TAG) classes. Moreover, HKL improved fatty acid oxidation in the kidneys of CKD rats. In conclusion, this study found that HKL can protect against adenine-induced CKD, possibly through the regulation of lipid metabolism.